Melanin’s Journey from Melanocytes to Keratinocytes: Uncovering the Molecular Mechanisms of Melanin Transfer and Processing - Bento-Lopes, Liliana (2023)
Funding This research was funded by Fundação para a Ciência e a Tecnologia (Portugal) grant number PTDC/BIA-CEL/29765/2017 and Ph.D. fellowships to L.B.-L., L.C.C., M.V.N. and J.C. (numbers SFRH/BD/131938/2017, 2020.08812.BD, PD/BD/137442/2018, and PD/BD/136905/2018, respectively). This work was also supported by iNOVA4Health—UIDB/04462/2020 and UIDP/04462/2020—and by the Associated Laboratory LS4FUTURE (LA/P/0087/2020), two programs financially supported by Fundação para a Ciência e a Tecnologia/Ministério da Ciência, Tecnologia e Ensino Superior (Portugal).